“Water, Water, Everywhere”: Hydro-Coloniality, Oceanic Agency, and Environmental Justice in S. T. Coleridge’s “The Rime of the Ancient Mariner” - Rumi, Syeda Masnuna; Islam, Md. Zohorul; Afreen, Sumaiya; Sultana, Samsad; Abtahee, Hazzaz Al; Khatun, Mst. Ayesha (Journal of Cultural Analysis and Social Change, 2026)
This paper aims to investigate Samuel Taylor Coleridge's "The Rime of the Ancient Mariner" from the perspective of hydro-colonialism. This paper argues that Colridge brings colonial violence and ecological justice through his compelling narrative. Hydro-colonialism, Blue Humanities, and Environmental Justice will serve as the theoretical framework of this study. The extensive emphasis on the colonial exploitation of water resources and their anthropocentric attitude is one of the central arguments of the paper. Moreover, this paper shows that the ocean and oceanic entities are not subordinate to colonial hubris. The ocean is an agentive force that takes revenge through stagnation, storms, and denying water after the destructive act of the Mariner. The more-than-human figure Albatross becomes the victim of vicious killing by the Mariner, suggesting the apparent indifference of the colonial power in destroying nature to extract and expand material gain. Additionally, this paper argues that the pain and suffering of the Mariner, as well as his attention to it, suggest a connection to environmental justice. This paper concludes by arguing that Colridge's ecological conscience predicted contemporary environmental degradation and called for action toward equitable coexistence for humans and nonhumans.